Need for Further Development in Service Life Modelling of Concrete Structures in Chloride Environment. (2017) - Markeset, Gro; Kioumarsi, Mahdi
Abstract: Designing concrete structures for a very long service life may have considerable economic and societal benefits including minimized material consumption over the long term, thus contribute to more sustainable solutions. However, such long service lives require determination and extrapolation of environmental loadings and material durability performance over a long period, as well as reliable and operational models for service life predictions. Codes and standards give deem-to-satisfied recommendations for intended working (service) life up to about 100 years. However, if higher working lives of 200 and 300 years are specified, as for monumental buildings, bridges and other important infrastructures, more in-depth service life predictions are required. This paper focuses on durability and service life predictions for reinforced concrete structures for working (service) life requirements above 100 years.